The Effect of Smartphone Addiction on Learning Motivation and Well-Being - Syakinah, Mutiara; Daulay, Nurussakinah (Jurnal Basicedu, 2022)
Smartphone is an alternative communication and information dissemination in today's digital era. There are advantages and disadvantages of smartphones as a means of communication, including the impact that makes many people addicted. This study aims to determine whether learning motivation and well-being affect smartphone addiction in students. This research method uses a quantitative approach. The subject of this research was carried out on students with a total of 228 students, using a cluster sampling technique. Methods Data collection was carried out using a Likert Scale consisting of a well-being scale, a learning motivation scale, and a smartphone addiction scale. The results showed that well-being and learning motivation had no significant effect on causing smartphone addiction in students.